ChemInform Abstract: A High‐Content Screening Platform with Fluorescent Chemical Probes for the Discovery of First‐in‐Class Therapeutics. Issue 30 (7th July 2016) - Jo, Ala; Jung, Jinjoo; Kim, Eunha; Park, Seung Bum
Abstract: Review: 86 refs.